The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1371/journal.ppat.1010185
|View full text |Cite|
|
Sign up to set email alerts
|

Interleukin-17 contributes to Ross River virus-induced arthritis and myositis

Abstract: Arthritogenic alphaviruses are mosquito-borne viruses that are a major cause of infectious arthropathies worldwide, and recent outbreaks of chikungunya virus and Ross River virus (RRV) infections highlight the need for robust intervention strategies. Alphaviral arthritis can persist for months after the initial acute disease, and is mediated by cellular immune responses. A common strategy to limit inflammation and pathology is to dampen the overwhelming inflammatory responses by modulating proinflammatory cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 129 publications
(155 reference statements)
0
7
0
Order By: Relevance
“…IL-17 can promote inflammatory cytokines such as TNF-α and IL-1 [134]. In mice, it has been shown that both CD4 and CD8 T cells remain within joint tissues even after RRV viral clearance [134]. This is similar to clinical CHIKV data, as humans and animals infected with CHIKV show an increased Th17 inflammatory response, marked by an increase in IL-6, IL-17, and IFN-α [133,[136][137][138].…”
Section: Joint Inflammation and Arthritis The Most Common Presentationmentioning
confidence: 67%
See 2 more Smart Citations
“…IL-17 can promote inflammatory cytokines such as TNF-α and IL-1 [134]. In mice, it has been shown that both CD4 and CD8 T cells remain within joint tissues even after RRV viral clearance [134]. This is similar to clinical CHIKV data, as humans and animals infected with CHIKV show an increased Th17 inflammatory response, marked by an increase in IL-6, IL-17, and IFN-α [133,[136][137][138].…”
Section: Joint Inflammation and Arthritis The Most Common Presentationmentioning
confidence: 67%
“…There are other alphaviruses which cause persistent joint pain, including Ross River virus (RRV), Barmah Forest virus (BFV), Mayaro virus (MAYV), and o'nyoung'nyoung virus (ONNV), which CHIKV is closely genetically related to [134,135]. In RRV, joint pain is associated with increased levels of IL-17 produced by T cells that circulate in host tissues to fend off the virus [134]. IL-17 can promote inflammatory cytokines such as TNF-α and IL-1 [134].…”
Section: Joint Inflammation and Arthritis The Most Common Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, however, IL-17A was observed at higher levels in RRV-infected MXRA8 −/− mice at 3 dpi. IL-17 has recently been shown to contribute to CHIKV and RRV disease ( 31 , 32 ). The upregulation of IL-17A at 3 dpi of RRVD suggests MXRA8 deficiency may alter T cell differentiation of the Th17 axis during the onset of RRVD.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, IL-17A has been reported to be associated with tissue inf lammation as well as neutrophil infiltration in CHIKV-induced RA [28]. In another recent study on IL-17 in RRV disease, IL-17 has been found to be responsible for RRV-induced arthritis and myositis [52]. IL-17 expression is up-regulated in musculoskeletal tissues and sera of RRV infected mice and humans.…”
Section: Alphavirus Disease and Host Immune Responsementioning
confidence: 96%